EFISIENSI BIAYA BAHAN BAKU MENGGUNAKAN METODE MRP UNTUK MEMINIMASI BIAYA INVENTORY DI CV. NUR RAHMAT TEKNIK - Juliansyah, Juliansyah; Aryanto, Aryanto; Syamsi, Wuri Arianty; Fauzi, Muchammad (LPPM Universitas Bina Bangsa, 2024)
This study aims to analyze the efficiency of raw material inventory management using the Material Requirements Planning (MRP) method to minimize inventory costs in CV. Nur Rahmat Teknik. The company faces the challenges of conventional inventory management, which often leads to excess or shortage of raw materials as well as high storage costs. This research method was carried out using a quantitative method with the data source used being secondary data through historical data of company requests. The MRP method in the study was applied to identify raw material needs based on historical demand data, calculate optimal order schedules, and evaluate their impact on inventory costs. Four forecasting methods were used, namely Double Moving Average, Double Exponential Smoothing from Brown, Double Exponential Smoothing From Holt, and Linear Regression, to determine the forecasting method used and the level of accuracy of predicting raw material needs. The lot sizing techniques used in this MRP method are Economic Order Quantity, Periodic Order Quantity, and Lot for Lot. The results show that the application of the MRP method significantly reduces inventory costs by optimizing the booking lot size and booking schedule. These findings provide valuable insights into more efficient inventory management, improving the company's competitiveness and profitability. Practical recommendations are given for the sustainable implementation of the MRP method in the company's operations